1985
DOI: 10.1111/j.1348-0421.1985.tb00877.x
|View full text |Cite
|
Sign up to set email alerts
|

Possible Involvement of Transglutaminase in Endocytosis and Antigen Presentation

Abstract: Experiments were carried out to determine as to whether or not internalization of antigen is necessary for subsequent antigen presentation by accessory cells using monoamines which are known as transglutaminase (TGase) inhibitors. It was found that endocytosis for immune complexes via Fe receptors such as sheep erythrocytes coated with IgG class antibody (EA) was different from receptorindependent endocytosis for soluble protein such as horse radish peroxidase (HRP) in the sensitivity to monoamines; methylamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1991
1991
2008
2008

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…The use of cytochalasins B and D has demonstrated that actin filaments also play a significant role in amoeba locomotion and phagocytosis (29,33). Methylamine is an inhibitor of transglutaminase, a plasma membrane enzyme involved in the aggregation of ligand-receptor complexes, and is required for receptor-mediated pinocytosis in fibroblasts and macrophages (20,35). This inhibitor has been used to inhibit adsorptive pinocytosis of Semliki Forest virus in BHK-21 cells and infection of McCoy cells by Chlamydia trachomatis (21,32).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of cytochalasins B and D has demonstrated that actin filaments also play a significant role in amoeba locomotion and phagocytosis (29,33). Methylamine is an inhibitor of transglutaminase, a plasma membrane enzyme involved in the aggregation of ligand-receptor complexes, and is required for receptor-mediated pinocytosis in fibroblasts and macrophages (20,35). This inhibitor has been used to inhibit adsorptive pinocytosis of Semliki Forest virus in BHK-21 cells and infection of McCoy cells by Chlamydia trachomatis (21,32).…”
Section: Discussionmentioning
confidence: 99%
“…Monoclonal antibodies against monocyte CR1 and CR3 receptors inhibited intracellular multiplication by abrogating L. pneumophila adherence and phagocytosis. In contrast, nonopsonized L. pneumophila have been shown to infect human monocytes and macrophages (17, 27) and amoebae (2,9,15,24,28,31,35). This phenomenon suggests that mechanisms other than complement-mediated phagocytosis are important in the uptake of L. pneumophila by both human phagocytes and amoebae.…”
mentioning
confidence: 99%
“…While bearing in mind that CD is an immune‐mediated disorder, it should also be noted that the activity of tTG has been associated with receptor‐mediated endocytosis (39), phagocytosis (40), antigen presentation (41,42), and differentiation of lymphocytes, monocytes, and B cells (43–45). It is particularly interesting that macrophages display increased tTG activity after inflammatory stimuli and that this increase in enzyme activity leads to enhanced Fc receptor‐mediated endocytosis in the macrophages (40,46).…”
Section: Structure and Functional Roles Of Tissue Transglutaminasementioning
confidence: 99%
“…Highly expressed in the sub‐epithelial cells of the gut, TGM2 exhibits strong affinity for gluten and is responsible for breaking it down when ingested. By cross‐linking glutamine with itself or other extracellular proteins, TGM2 creates aggregates, which are readily recognized and taken up by the antigen‐presenting cells of the immune system [Teshigawara et al, 1985]. Deamidation enhances the binding affinity of gluten T‐cell epitopes to the major histocompatibility complex (MHC) class II molecules, such as HLA‐DQ2 or HLA‐DQ8, to present the disease‐related epitopes to CD4+T cells for antibody production.…”
Section: Introductionmentioning
confidence: 99%